62.5k views
3 votes
You are given the exponential function g(x) = 3 x . Which option below gives the formula for a new function h created by stretching g by a factor of 3 along the y-axis?

h(x) = 3x+1

h(x) = 3x-1

h(x) = x · 3x+1

h(x) = x · 3x-1

User Dvtoever
by
5.4k points

2 Answers

3 votes

Answer:

A

Explanation:

User Masher
by
5.2k points
2 votes

Answer:

A.
h(x) = 3^(x+1)

Explanation:

Stretching means that original function is multiplied by a constant, which is equal to 3 in this case:


h(x) = 3 \cdot g (x)


h(x) = 3\cdot 3^(x)


h(x) = 3^(x+1)

The answer is A.

User Jannis
by
4.3k points